2019
DOI: 10.1016/j.jcmgh.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Drives Growth Factor–Independent Esophageal Cancer Proliferation via Phosphohistidine–Focal Adhesion Kinase Signaling

Abstract: Background & Aims Most targeted therapies against cancer are designed to block growth factor–stimulated oncogenic growth. However, response rates are low, and resistance to therapy is high. One mechanism might relate to the ability of tumor cells to induce growth factor–independent proliferation (GFIP). This project aims to understand how (1) cancer cells preferentially derive a major growth advantage by using critical metabolic products of glucose, such as phosphoenolpyruvate (PEP), to drive prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The cells were incubated in growth factor-free (serum-free), but high glucose (25 mM) and 2 mM L-alanyl-L-glutamine (GlutaMAX TM ) containing DMEM for various time periods (24, 48, 72 h) and, thereafter, the incorporation of BrdU as measure for proliferation evaluated. As earlier published data show that tumor cells and non-cancerous cells proliferate growth-factor independent with high glucose and a stable, viability increasing glutamine source [5255], those conditions have been used herein for all cell types to avoid artificial data obtained by exogenous growth factors originating from the serum. Furthermore, it was shown that starvation of tumor cells often results in autophagy-activated cell proliferation [56].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were incubated in growth factor-free (serum-free), but high glucose (25 mM) and 2 mM L-alanyl-L-glutamine (GlutaMAX TM ) containing DMEM for various time periods (24, 48, 72 h) and, thereafter, the incorporation of BrdU as measure for proliferation evaluated. As earlier published data show that tumor cells and non-cancerous cells proliferate growth-factor independent with high glucose and a stable, viability increasing glutamine source [5255], those conditions have been used herein for all cell types to avoid artificial data obtained by exogenous growth factors originating from the serum. Furthermore, it was shown that starvation of tumor cells often results in autophagy-activated cell proliferation [56].…”
Section: Resultsmentioning
confidence: 99%
“…The identities of the pHis proteins we identified suggest that pHis may play a role in mammalian cell signaling [32][33][34] . Indeed, a direct correlation of pHis protein levels with carcinogenesis has recently been reported 30,[35][36][37] . Interestingly, we identified 20 N-phosphate sites on proteins that were reported to be enriched by IAP by Hindupur et al from mTOR-driven hepatocellular carcinoma mouse tumors as potential LHPP substrates, including BCLAF1, which in our studies was found to contain pLys (K391) with a reasonable probability of localization of 79.6%.…”
Section: Discussionmentioning
confidence: 95%
“…The human LHPP gene (NM_022126) is located on chromosome 10 (10q26.13). It is an acidic protein containing 270 amino acids and is a nontransmembrane protein which is mainly located in the cytoplasm and is expressed in most tissues [8][9][10]. Previous studies have found that LHPP is a genetic marker of alcohol dependence and severe depression and is related to mitochondrial dysfunction and chronic oxidative stress [10,11].…”
Section: Introductionmentioning
confidence: 99%